PENGARUH DAYA DUKUNG LINGKUNGAN DAN STRATEGI ADAPTASI MITIGASI TERHADAP KAPASITAS ADAPTIF PETERNAKAN SAPI POTONG DI DESA NAEKASA KECAMATAN TASIFETO BARAT KABUPATEN BELU - Bruno Oktavianus Bria; Ture Simamora; Oktovianus Tabenu; Simon Juan Kune (Kandang : Jurnal Peternakan, 2026)
This study aims to analyze environmental carrying capacity, mitigation adaptation strategies, and the adaptive capacity of beef cattle farmers, as well as the influence of environmental carrying capacity and mitigation adaptation strategies on the adaptive capacity of beef cattle farms in Naekasa Village, West Tasifeto District, Belu Regency. The background of this study is based on the condition of beef cattle farms that still face various obstacles, such as limited feed, suboptimal waste management, climate change, and limited access to technology, information, and markets. These conditions influence livestock farming business terminations and the adaptive capacity of farmers in the face of environmental changes. This study was conducted from July to August 2025 using survey methods and a quantitative approach. The population in this study were all 70 members of the Permatasari cattle breeder group in Naekasa Village, while the sample used was 60 respondents using a census technique. The data used consisted of primary data obtained through observation, interviews, questionnaires, documentation, and recording, as well as secondary data from relevant agencies. Data analysis was conducted using descriptive percentage analysis with a Likert scale and multiple linear regression analysis. The results showed that environmental carrying capacity was in the moderate category, especially in the aspects of land and natural resource utilization (58.3%), feed availability and quality (58.3%), livestock waste management (60%), environmental impacts of livestock (60%), and climate change mitigation (63.3%). Adaptation and mitigation strategies were also in the moderate category, indicating that farmers have made efforts to adapt to environmental changes, although not optimally. The adaptive capacity of livestock farmers was generally in the moderate category, reflecting that farmers were quite capable of maintaining their livestock businesses, but still needed to strengthen aspects of innovation, partnerships, and business diversification. The results of the multiple linear regression analysis showed that environmental carrying capacity and adaptation and mitigation strategies had a positive and significant influence on the adaptive capacity of beef cattle farming. The better the environmental carrying capacity and the stronger the adaptation and mitigation strategies implemented, the greater the farmers' adaptive capacity to face the challenges of climate change and stop livestock farming.